The waiting place : when home is lost and a new one not yet found - Nayeri, Dina (Candlewick Press, 2022)
Explores the plight of refugee children from around the world in camps the author calls the Waiting Place--a place that seems to offer shelter and comfort, but is really a trap, a pause on the lives and dreams of refugee children. Showcases photographs of such camps and children and relates their stories, telling of lost education and opportunities, but also looking forward in hope to a time when the world will begin to take the refugee crisis seriously. Includes a glossary.